APPLICATION OF RISK MANAGEMENT AND TIME STUDY TO TOTAL COMPENSATION DESIGN: CASE STUDY OF FA BERSAUDARA AS PARTNER OF LG ELECTRONIC INDONESIA - Akbar, Fadjrin; Wiryono, Sudarso Kaderi (Journal of Business and Management, 2017)
Abstract. LG Electronic Indonesia (LGEI), one of popular electronics brand in Indonesia created a new system in aftersales service section. The new system is making the aftersales divisions separated from LG Electronic Indonesia and it is handled now by a third party as Authorized Service Center (ASC). In this current conditions, FA Bersaudara has many service delays in every month that could not be finished. From the early research showing the employees unsatisfied with current compensation design system. So that, this research is provided to design the compensation system especially cash compensation that could increase the employees’ satisfaction with time study and risk management approach. Time study is being focused on because this theory is giving more fairness with detained compensation based on level of job. The risk management will focus on the cost that can be maintained by company to pay to employees as the part of the total compensation. This research use the Microsoft excel as software to calculating the number of standard time and also expected value from risks. From this research, it can be concluded that the total compensation is based on basic salary, fuel and food compensation, working time and other related risks. These factors may be different with prior compensation system which compensation is solely based on two factors which are basic salary and fuel and food compensation with no regards of working time and other related risks. There is significant difference between compensation system with standardized time calculation and risk and compensation system with no consideration in calculating related risk and standardized working time. The cost that raised from risk adjustment can be mitigated by using non-insurance transfer and insurance methods. Keywords: compensation, time study, risk management